2017
DOI: 10.1016/j.athoracsur.2017.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Resection for Second Lung Cancer After Pneumonectomy: A Population-Based Study

Abstract: On the basis of our analysis of the SEER database, sublobar resection can be performed in selected patients with small tumors (≤2 cm) and early-stage disease (stage I/II). Although perioperative mortality is significant, the favorable 1-year and 3-year survival may justify the role of an additional procedure on the single lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(56 citation statements)
references
References 16 publications
2
53
1
Order By: Relevance
“…It was found that the survival rate was better for metachronous than for metastatic cancer (12). In a wider cohort of patients, Ayub et al (13) found that sublobar resection had higher median overall survival than did those who underwent lobectomy (42 vs. 18 months); median survival after resection for metachronous tumors was higher than after resection for metastatic cancers (40 vs. 28 months). This study lacks information about patients' functional status, cardiopulmonary reserves, comorbidities, surgical approach (open vs. minimally invasive, type of thoracotomy) and reported at not negligible 1-and 3-month mortality (respectively, 11.1% and 12.7%).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the survival rate was better for metachronous than for metastatic cancer (12). In a wider cohort of patients, Ayub et al (13) found that sublobar resection had higher median overall survival than did those who underwent lobectomy (42 vs. 18 months); median survival after resection for metachronous tumors was higher than after resection for metastatic cancers (40 vs. 28 months). This study lacks information about patients' functional status, cardiopulmonary reserves, comorbidities, surgical approach (open vs. minimally invasive, type of thoracotomy) and reported at not negligible 1-and 3-month mortality (respectively, 11.1% and 12.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The standard surgical treatment for primary lung cancer is lobectomy; however, 3%-7% of patients with lung cancer require pneumonectomy. 1,2 Reports show that the risk of tumor recurrence after complete resection of lung cancer is 2%-5% per year, 3,4 depending on the stage. Moreover, metachronous lung cancer occurs in 1%-5% of cases of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…8 Pneumonectomy has been reported to increase the total vascular resistance of the pulmonary circulation and may increase the right ventricular load 9 ; therefore, a history of pneumonectomy is considered a relative contraindication for further pulmonary resection. 2 Careful intraoperative respiratory management is essential during contralateral pulmonary resection in postpneumonectomy patients. During normal respiratory management, the operative field is suboptimal due to ventilation of the operative side 10 ; therefore, thoracotomy is performed in most patients.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in early detection technology of lung cancer and the close postoperative follow-up of lung cancer patients, the detection rate of second primary lung cancer (SPLC) has been growing. The e cacy and safety of surgical treatment for second primary non-small cell lung cancer (SP-NSCLC) patients have also been demonstrated in several studies [1][2][3][4][5][6][7]. For the patients with resectable earlystage NSCLC, lobectomy remains the accepted standard surgical procedure [8].…”
Section: Introductionmentioning
confidence: 99%